2001
DOI: 10.1177/109634800102500304
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Slot Operations of a Hotel Casino in the Las Vegas Locals’ Market

Abstract: This exploratory study was designed to identify and explain the sources of variation in the daily slot handle of a locals' market hotel casino in Las Vegas, Nevada. A regression model was used to analyze the effects of temporal, operational, and marketing variables hypothesized to influence slot handle. A simultaneous regression analysis was conducted with audited, secondary data using variables adapted from prior research. Significance tests were conducted at the .05 alpha level. The model failed to produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
5
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 11 publications
9
55
5
1
Order By: Relevance
“…However, Resort 2's drop-byday graph indicated Tuesday as the day with the greatest average cash drop. This appeared to be an unusual result for a casino data set, given the consistency of elevated weekend gaming volumes in other studies (Lucas and Bowen, 2002;Lucas and Brewer, 2001;Lucas et al, 2006). Although the management of Resort 2 offered no explanation for this condition, they did verify the accuracy of the data.…”
Section: Data Screeningmentioning
confidence: 64%
See 1 more Smart Citation
“…However, Resort 2's drop-byday graph indicated Tuesday as the day with the greatest average cash drop. This appeared to be an unusual result for a casino data set, given the consistency of elevated weekend gaming volumes in other studies (Lucas and Bowen, 2002;Lucas and Brewer, 2001;Lucas et al, 2006). Although the management of Resort 2 offered no explanation for this condition, they did verify the accuracy of the data.…”
Section: Data Screeningmentioning
confidence: 64%
“…In gaming, Lucas and Brewer (2001) found that a variable representing daily restaurant headcounts failed to produce a significant and positive model effect on slot machine coin-in levels. This result was most troubling, as management had condoned multimillion-dollar, annual, operating losses in the food department, based on the belief that the restaurants produced a substantial indirect effect on gaming volumes.…”
Section: Cherry-pickingmentioning
confidence: 96%
“…Most of the work related to the discovery of influences on slot machine business volume has been performed at the aggregate level (Lucas and Brewer, 2001;Lucas and Bowen, 2002;Lucas and Santos, 2003). These studies all featured a dependent variable measured in terms of daily coin-in, which represented the total amount of wagers accepted in all slot machines.…”
Section: Slot Performance Literaturementioning
confidence: 99%
“…Many studies of slot performance and the factors leading to better slot business have been conducted in the Western context (Christopherson and Weatherly, 2006;Lucas and Brewer, 2001;Lucas et al, 2004;Lucas and Roehl, 2002), with little research carried out in Asia, including Macau, which has a very different customer base from casinos elsewhere. This study fills the research gaps in this area by exploring the factors that discourage slot play in Macau's casinos.…”
Section: Introductionmentioning
confidence: 98%